The Use of Social Media Among Indigenous Communities In Improving The Economy Towards The Progress of The Modern Era Based on The Republic of Indonesia Law No. 19 of 2016 Concerning Amendments To Law No. 11 of 2008 Concerning Electronic Information And Transactions - Gatot Efrianto; Nia Tresnawaty (KRTHA BHAYANGKARA, 2024)
Social media, also known as social networks, is part of new media. It's clear that the interactive content in new media is very high. Social media, quoted from Wikipedia, is defined as an online media, where users can easily participate, share, and create content including blogs, social networks, wikis, forums, and virtual worlds. Blogs, social networks, and wikis are the most common forms of social media used by people around the world. Social media has a significant influence on societal changes regarding their personalities. The purpose of this research is to determine the implementation of Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Electronic Information and Transactions, the application of sanctions for social media users who harm others. This research study is normative juridical in nature as the main approach, considering that the discussion is based on legislation and legal principles applicable to issues of information technology crimes. The juridical approach is intended to conduct an assessment of the legal field, especially criminal law. Most social media users who intend to harm others in their use of social media will be ensnared by Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 on Electronic Information and Transactions (ITE Law), whether intentional or unintentional. The law should provide protection to internet users by thinking positively, having good intentions, and taking decisive action against cybercrime perpetrators. However, the legal system has not yet addressed all computer crimes through the Internet. The ITE Law is expected to provide guidelines in restricting the use of social media for the public.Top of Form